Penerapan Cooperative Learning Tipe Students Team Achievement Division (STAD) Berbasis Media Kahoot untuk Meningkatkan Keaktifan Belajar Peserta Didik - Rusyda, Nurislami Rusyda; Prayitno, Sudi; Mustiani (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study is a Classroom Action Research (CAR) aimed at improving students’ learning activeness in Mathematics through the implementation of the cooperative learning model Students Team Achievement Division (STAD) integrated with Kahoot media. The subjects of this research were 30 students of class VII-9 at SMPN 4 Mataram. The study was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected through observation and documentation, while data analysis was carried out using descriptive qualitative and quantitative methods. The results showed an increase in students’ learning activeness from the first cycle to the second cycle. In the first cycle, the percentage of student activeness reached 66.67% and increased to 86.67% in the second cycle. This improvement indicates that the implementation of the STAD cooperative learning model combined with Kahoot successfully created a more enjoyable, interactive, and engaging learning atmosphere. Therefore, it can be concluded that this strategy is effective in enhancing students’ activeness in learning Mathematics.